It looks like the limit you want to find is
![\displaystyle \lim_(x\to\infty) \left((x+4)/(x-1)\right)^(x+4)](https://img.qammunity.org/2022/formulas/mathematics/college/v414zaaup3v1fr2ci9j8nwb6v0f47i24i4.png)
One way to compute this limit relies only on the definition of the constant e and some basic properties of limits. In particular,
![e = \displaystyle\lim_(x\to\infty)\left(1+\frac1x\right)^x](https://img.qammunity.org/2022/formulas/mathematics/college/ewpa5dcit8vpeg04goby3f5giaelxfnvrq.png)
The idea is to recast the given limit to make it resemble this definition. The definition contains a fraction with x as its denominator. If we expand the fraction in the given limand, we have a denominator of x - 1. So we rewrite everything in terms of x - 1 :
![\left((x+4)/(x-1)\right)^(x+4) = \left((x-1+5)/(x-1)\right)^(x-1+5) \\\\ = \left(1+\frac5{x-1}\right)^(x-1+5) \\\\ =\left(1+\frac5{x-1}\right)^(x-1) * \left(1+\frac5{x-1}\right)^5](https://img.qammunity.org/2022/formulas/mathematics/college/k1rms3nb7pr0fiitxf203tv5uz61notrp5.png)
Now in the first term of this product, we substitute y = (x - 1)/5 :
![\left((x+4)/(x-1)\right)^(x+4) = \left(1+\frac1y\right)^(5y) * \left(1+\frac5{x-1}\right)^5](https://img.qammunity.org/2022/formulas/mathematics/college/td9uc2fzhb5tuaed7eiaol1382vfoo8p5r.png)
Then use a property of exponentiation to write this as
![\left((x+4)/(x-1)\right)^(x+4) = \left(\left(1+\frac1y\right)^y\right)^5 * \left(1+\frac5{x-1}\right)^5](https://img.qammunity.org/2022/formulas/mathematics/college/k8v92mozj58egdpty29vt9akvu3uzbs8dn.png)
In terms of end behavior, (x - 1)/5 and x behave the same way because they both approach ∞ at a proportional rate, so we can essentially y with x. Then by applying some limit properties, we have
![\displaystyle \lim_(x\to\infty) \left((x+4)/(x-1)\right)^(x+4) = \lim_(x\to\infty) \left(\left(1+\frac1x\right)^x\right)^5 * \left(1+\frac5{x-1}\right)^5 \\\\ = \lim_(x\to\infty)\left(\left(1+\frac1x\right)^x\right)^5 * \lim_(x\to\infty)\left(1+\frac5{x-1}\right)^5 \\\\ =\left(\lim_(x\to\infty)\left(1+\frac1x\right)^x\right)^5 * \left(\lim_(x\to\infty)\left(1+\frac5{x-1}\right)\right)^5](https://img.qammunity.org/2022/formulas/mathematics/college/9rvs7h46q1oh5vfir4jsefd085uy8hswjm.png)
By definition, the first limit is e and the second limit is 1, so that
![\displaystyle \lim_(x\to\infty) \left((x+4)/(x-1)\right)^(x+4) = e^5*1^5 = \boxed{e^5}](https://img.qammunity.org/2022/formulas/mathematics/college/6hntad6hn780q8jiu2cd9qr1j31mmwpvkq.png)
You can also use L'Hopital's rule to compute it. Evaluating the limit "directly" at infinity results in the indeterminate form
.
Rewrite
![\left((x+4)/(x-1)\right)^(x+4) = \exp\left((x+4)\ln(x+4)/(x-1)\right)](https://img.qammunity.org/2022/formulas/mathematics/college/es4t0epayp4fzgiayqn0otmm1wz23pkn3g.png)
so that
![\displaystyle \lim_(x\to\infty) \left((x+4)/(x-1)\right)^(x+4) = \lim_(x\to\infty)\exp\left((x+4)\ln(x+4)/(x-1)\right) \\\\ = \exp\left(\lim_(x\to\infty)(x+4)\ln(x+4)/(x-1)\right) \\\\ =\exp\left(\lim_(x\to\infty)\frac{\ln(x+4)/(x-1)}{\frac1{x+4}}\right)](https://img.qammunity.org/2022/formulas/mathematics/college/ldf7yxkphu4x4s9v1h1m4adr9he6g0u91c.png)
and now evaluating "directly" at infinity gives the indeterminate form 0/0, making the limit ready for L'Hopital's rule.
We have
![(\mathrm d)/(\mathrm dx)\left[\ln(x+4)/(x-1)\right] = -\frac5{(x-1)^2}*(1)/((x+4)/(x-1)) = -\frac5{(x-1)(x+4)}](https://img.qammunity.org/2022/formulas/mathematics/college/azkucaebfr8fleuxx96hu6o08qy0y3m2ti.png)
![(\mathrm d)/(\mathrm dx)\left[\frac1{x+4}\right]=-\frac1{(x+4)^2}](https://img.qammunity.org/2022/formulas/mathematics/college/le948gnxfzlwf1lesxdzgu470oso8dxzg7.png)
and so
![\displaystyle \exp\left(\lim_(x\to\infty)\frac{\ln(x+4)/(x-1)}{\frac1{x+4}}\right) = \exp\left(\lim_(x\to\infty)\frac{-\frac5{(x-1)(x+4)}}{-\frac1{(x+4)^2}}\right) \\\\ = \exp\left(5\lim_(x\to\infty)(x+4)/(x-1)\right) \\\\ = \exp(5) = \boxed{e^5}](https://img.qammunity.org/2022/formulas/mathematics/college/uw91qg45wmml300onenr18dctg4sb3o6ep.png)